CS-MAP in Agusan Del Norte: Presentation of Initial Results and Validation - Gutierrez, Mary Anne; Garcia, Cornelia A.; Raviz, Jeny V. (2024)
Agusan Del Norte, a province in the Caraga Region of the Philippines, faces increasing climate variability, particularly flooding and drought. To address these challenges, the CGIAR Research Initiative on Climate Resilience (ClimBeR) has implemented the Climate-Smart Mapping and Adaptation Planning (CS-MAP), a participatory mapping approach developed by CCAFS-SEA. CS-MAP is designed to assess climate-related risks, map vulnerable areas, and develop location-specific adaptation plans. This presentation shared the preliminary findings with partners and stakeholders in Agusan Del Norte, including climate risk maps and consolidated adaptation plans, aiming to gather further input for consultation and validation.